Comparing the Effects of Genistein, Silymarin, Lecithin on Improved Liver Necrosis Induced by Paracetamol Toxic Dose Administration in Rattus novergicus Wistar Strain - Syifa Mustika; Supriono Supriono; Bogi Pratomo; Harijono Achmad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: Paracetamol, a widely used antipyretic and analgesic drug has been known for its side effect of liver toxicity resulting from free radical formation leading to necrotic hepatocytes. Oral genistein may reduce lipid peroxidation and increase total antioxidant capacity in liver. The present study was aimed to compare the effects of administering genistein, silymarin and lecithin on improved necrotic hepatocytes in Wistar rats fed with toxic dose of paracetamol. Method: An experimental study was conducted at the Laboratory of Physiology and Anatomical Pathology, University of Brawijaya between May and September 2011. About 48 male rats were categorized into 4 groups. The first group was treated with 600 mg/kgBW of oral paracetamol. The other groups were treated with 600 mg/kgBW paracetamol and additional 2 mg/kgBW genistein, 50 mg/kgBW silymarin or 100 mg/kgBW lecithin. ALT, AST, bile acid, malondialdehyde (MDA) and glutation (GSH) levels were measured and centrilobular necrosis observed by histopathological examination. Data were analyzed statistically by ANOVA. Results: AST and ALT level were significantly lower in genistein group (p = 0.004 and p = 0.001). The lowest bile acid level was found in the lecithin group (p = 0.025); while lowest MDA level was found in silymarin group (p = 0.009). The highest GSH level was found in lecithin group (p = 0.001). The lowest percentage of centrilobular necrosis was found in genistein group (p = 0.001). Conclusion: Genistein, silymarin and lecithin supplementation improve liver necrosis induced by toxic dose of paracetamol. Among them, genistein is the most significant agent. Keywords: genistein, silymarin, lecithin, paracetamol, hepatotoxicity